2020
DOI: 10.1177/0263617420916592
|View full text |Cite
|
Sign up to set email alerts
|

Application of response surface methodology for optimization of zinc elimination from a polluted soil using tartaric acid

Abstract: Heavy metal wastes generated from mining activities are a major concern in developing countries such as Iran. Increasing concentrations of these metals in the soil make up a severe health hazard due to their non-degradability and toxicity. In this study, batch washing experiments were conducted in order to investigate the removal efficiency of zinc by biodegradable chelates, tartaric acid. For this purpose, soil samples were collected from the zinc contaminated soil in the region of the Angouran, Zanjan, Iran.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…The Fisher variation ratio ( F -value), probability of error value ( p -value), lack of fit and adequate precision were all evidence of ANOVA. Generally, the p -value (probability of error value) less than 0.05 suggested that terms of the model were significant. , The high F -value of 31.11 and the p -value below 0.0001 implied that the model was significant and adequate in the washing process . Moreover, the small value of coefficient of variation (CV, %) suggested that the acceptable variation and reproducibility of the model for the further prediction of Zn removal within the range of research variables. , Additionally, it was desirable that an appropriate regression model had a greater adequate precision (>4.0), which was used for representing the signal-to-noise ratio .…”
Section: Resultsmentioning
confidence: 99%
“…The Fisher variation ratio ( F -value), probability of error value ( p -value), lack of fit and adequate precision were all evidence of ANOVA. Generally, the p -value (probability of error value) less than 0.05 suggested that terms of the model were significant. , The high F -value of 31.11 and the p -value below 0.0001 implied that the model was significant and adequate in the washing process . Moreover, the small value of coefficient of variation (CV, %) suggested that the acceptable variation and reproducibility of the model for the further prediction of Zn removal within the range of research variables. , Additionally, it was desirable that an appropriate regression model had a greater adequate precision (>4.0), which was used for representing the signal-to-noise ratio .…”
Section: Resultsmentioning
confidence: 99%
“…The linear model terms (A, B, C), the interaction term AC and quadratic terms C 2 are statistically significant (p < 0.05). This is to say that the number of experiments carried out was sufficient to illustrate the influence of the operating variables on the amount of p-NA adsorbed from an aqueous solution [23][24][25] . The plot of actual against predicted response values of p-NA removal onto TiO 2 -FSAC is given in Figure 3.…”
Section: Anova Resultsmentioning
confidence: 99%
“…One of the RSMs, central composite design (CCD), is the most widely used statistical method based on the multivariate nonlinear model for the optimization of process variables, and was applied to determine the regression model equations for the prediction. For multivariate optimization, CCD offers the advantage of enabling effective and time-saving optimization by reducing the total number of experimental runs required over the conventional one-factor-at-a-time method [ 19 ].…”
Section: Resultsmentioning
confidence: 99%